Shear load capacity prediction of unperforated and perforated partially grouted masonry walls. (1st April 2022) - Medeiros, Klaus A.S.; Parsekian, Guilherme A.; Shrive, Nigel G.; Fonseca, Fernando S.
Highlights: Use of a robust database comprising numerical and experimental specimens. Different existing shear equations are evaluated. Current design codes predict inaccurately the shear strength of walls. A new equation for shear prediction of partially grouted walls is proposed. Shear strength of multi-story perforated partially grouted walls is discussed. Abstract: Accurate prediction of the shear load capacity (SLC) of partially grouted masonry walls (PGMW) remains challenging due to the complex behavior of the material which depends on various parameters. Relevant existing shear equations, including the equations of the TMS 402/602 (2016) and the CSA S304 (2014), are evaluated, and a new equation is proposed. Different approaches are examined to determine the most consistent way of predicting the SLC of single and multi-story PGMW with openings. The database used in this research is comprised of 96 masonry walls created through numerical simulation using the finite element method (FEM) and 59 experimental masonry walls reported in the literature. Statistical analysis shows that the new proposed equation performs more precisely than the other shear equations and highlights the necessity of updating the expressions in TMS 402/602 (2016) and the CSA S304 (2014) since their equations made the most inaccurate predictions of those assessed. Furthermore, the results confirm that is unsafe to calculate the SLC of a wall ignoring the openings. In this context, the most accurate predictions for the perforated walls were made using the proposed equation considering the strength of the wall as the sum of the strength of the wall piers with dimensions defined by the openings of the same story.